Clinical outcomes of adjuvant radiotherapy for nodal negative T1 and T2 breast cancer - ALSAN ÇETİN, İLKNUR (My University, 2022)
The objective of this study was to determine the long -term results of postoperative radiotherapy (RT) in patients with node -negative T1 –T2 breast cancer and the prognostic factors affecting these results. Materials and Methods : We retrospectively evaluated 382 node -negative breast cancer patients (pT1a –c, T2) treated with surgery. All patients underwent postoperative RT and 80% of patients received hormone therapy. Prognostic variables included patient characteristics, disease characteristics, and intervention factors. The primary endpoint was overall survival (OS). Survival curves were estimated using the Kaplan –Meier method. Differences in observed survival distributions among patient subgroups were evaluated using a two -sided long -rank test. We applied univariate and multivariate Cox models to evaluate predictive factors. Statistical significance was evaluated at a level of P < 0.05. Results : The median follow -up was 143 months. The 10 -, 15 -, and 20 - year OS rates were 92%, 86%, and 80%, respectively. Univariate analysis showed that age (< 45, 45 –65, > 65 years; P < 0.0001), comorbidity (P = 0.008), menopausal status (P = 0.03), and tumor stage (T1a –c, T2; P = 0.006) (table 1) were significant predictors of OS. Multivariate analysis showed that age (< 45, 45 –65, > 65; P = 0.01) and tumor stage (T1a –c, T2; P < 0.0001) were independent predictors of OS. At age 15 years, the OS rate of patients with T1b, T1c, or T2 stage cancer was 87.5%, 81%, or 77%, respectively. Conclusions : Age and tumor stage were independent prognostic factors for women with node -negative early breast cancer.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; Early-stage breast cancer; prognostic factors; radiotherapy; survival; COMPARING TOTAL MASTECTOMY; 20-YEAR FOLLOW-UP; CONSERVING SURGERY; POSTOPERATIVE RADIOTHERAPY; SECTOR RESECTION; IRRADIATION; WOMEN; LUMPECTOMY; SURVIVAL; TRIAL; Early-stage breast cancer; prognostic factors; radiotherapy; survival